Pantoea agglomerans: An Emerging Pathogen in Hospitals and Foods, a narrative review - Omid Pouresmaeil; Jalal Mardaneh (Reviews in Clinical Medicine, 2024)
AbstractPantoea agglomerans is a Gram-negative rod that forms aggregates in liquid media. It is known for causing opportunistic infections in humans, especially in hospital settings and wounds from plant materials. The bacterium can lead to various infections like arthritis, endophthalmitis, and bacteremia, often from wooden splinters or plant thorns. Infections are diverse and affect immunocompromised individuals but respond well to antibiotics. P. agglomerans can be identified by its morphological characteristics and growth preferences in the lab. Resistance to Fosfomycin can aid in identification. Treatment typically involves antibiotics like imipenem and fluoroquinolones. Hospital-acquired infections from P. agglomerans have been linked to scenarios like endocarditis and septicemia. Selective culture media are crucial for isolating Pantoea species from clinical specimens. Regarding the treatment of infections induced by P. agglomerans, it is noteworthy that this bacterium generally exhibits susceptibility to a broad spectrum of antibiotics. Notably, these include but are not limited to imipenem, fluoroquinolones (e.g., ciprofloxacin and ofloxacin), aminoglycosides (e.g., amikacin, gentamicin, and tobramycin), broad-spectrum cephalosporins, and trimethoprim-sulfamethoxazole